The pregnancy outcomes in patients with epididymal obstructive azoospermia after microsurgical vasoepididymostomy: a systematic review and meta-analysis - Wang, Zilong; Wang, Xinkun; Song, Changze; Lu, Fuding; Zhai, Jiawen; Li, Naifa; Jiang, Baohong; Tan, Senbao; Xuan, Xujun (Frontiers in Medicine, 2023)
Purpose: Pregnancy outcomes (overall patency rate, overall pregnancy rate, natural pregnancy rate and the ratio of patients with pregnancy by assisted reproductive technology) after microsurgical vasoepididymostomy (MVE) in patients with epididymal obstructive azoospermia (EOA) were assessed through meta-analysis. Method: We searched PubMed, Embase, Web Science and the Cochrane Library databases up to September 28th, 2022 for published literature related to retrospective or prospective clinical studies of obstructive azoospermia after apparent microsurgical vasoepididymostomy. Our search terms included Obstructive Azoospermia, Epididymis Obstruction, Epididymal Obstruction and Vasoepididymostomy, Epididymovasostomy. Two researchers independently performed the literature search and assessed the eligibility of selected studies according to established inclusion criteria. The meta-analysis was performed using RevMan 5.4 software. Result: A total of 504 patients with EOA were included in ten studies (including 2 prospective clinical studies and 8 retrospective clinical studies). The mean patency rate after MVE was 72% (95%CI 68%-76%). The overall pregnancy rate was 34% (95%CI 30%-38%). The natural pregnancy rate is 21% (95%CI 17%-24%). And the ratio of patients with pregnancy by assisted reproductive technology (ART) was 34.9%. For the factors of affecting pregnancy outcomes after MVE, the overall pregnancy rates in patients receiving bilateral MVE were significantly higher than those receiving unilateral MVE (75.4% vs. 24.6%). The mean best sperm count and sperm motility in patients with overall pregnancy were significantly higher than those failing to pregnancy. For the subgroup meta-analysis revealed of microsurgical vasoepididymostomy, there were no statistically significant differences in the overall patency rate (68% vs. 70%), the overall pregnancy rate (33% vs. 37%), the natural pregnancy rate (20% vs. 23%) and the ratio of ART (30% vs. 28%) in end-to-side or end-to-end anastomosis and longitudinal or triangular intussusception MVE. Conclusion: Vasectomy patency rates are higher but natural pregnancy rates are lower in EOA male infertility patients after MVE. Altering the MVE procedures alone does not significantly improve pregnancy outcomes, but ART after MVE could improve the chance of pregnancy regardless of sperm parameters. We recommended that human sperms from EOA male infertility patients should be cryopreserved during intraoperative MVE for application in subsequent ICSI treatment procedure.